Spoofing’s Selection and Compensation in the Global Navigation Satellite System Consumer Navigation Equipment with Multi-Channel Antenna System - H. Kh. Saad; M. A. Loban (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A method for selecting spoofing signals in consumer equipment with a multichannel antenna system is proposed. The method provides for consistent filtering of the received signals at the outputs of all antenna system elements and by ranging codes of all navigation satellites, detection and measurement of the time delay of the true and false navigation signals in each code channel by the output signal of one of the antenna system elements, measurement of the phase difference of the signals at the outputs of the antenna system elements and the selected reference element for the estimated time delay in each channel by code. Compensation of spoofing signals is carried out in the spatial domain by estimating the correlation matrix of processes at the outputs of the antenna system channels by the corresponding countdown of code channel signals after matched filtering and forming of a weight vector while minimizing the output power of spoofing signals by directly inverting the estimate of the correlation matrix and carrying out weight processing of the adopted implementation. The simulation results are presented, confirming the efficiency of the method.